2023
DOI: 10.3390/pr11030856
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Pressure Fluctuations in Centrifugal Pumps without or with Clearance Flow

Abstract: As crucial equipment in the industrial field, the stable operation of centrifugal pumps has drawn noteworthy attention. Relevant studies in the open literature have shown that intense pressure fluctuations have a major effect on the reliability and lifetime of centrifugal pumps. In the present paper, the pressure fluctuations in the centrifugal pumps are discussed in detail from different perspectives. The details of the studies are as follows. Firstly, the pressure fluctuation characteristics in centrifugal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 103 publications
0
1
0
Order By: Relevance
“…Liu et al [8] conducted experiments and numerical simulations to characterize the energy and pressure pulsation of centrifugal pumps and explained the influence of axial distance on the pressure pulsation of the pump device. At the same time, in order to reduce the impact of pressure fluctuations on centrifugal pumps, Zheng et al [9] summarized measures to reduce pressure fluctuations and stress. Feng et al [10] found through research that the rotor-stator interaction in axial flow pumps can generate pressure pulsation and further vibration.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [8] conducted experiments and numerical simulations to characterize the energy and pressure pulsation of centrifugal pumps and explained the influence of axial distance on the pressure pulsation of the pump device. At the same time, in order to reduce the impact of pressure fluctuations on centrifugal pumps, Zheng et al [9] summarized measures to reduce pressure fluctuations and stress. Feng et al [10] found through research that the rotor-stator interaction in axial flow pumps can generate pressure pulsation and further vibration.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to study the total pressure and pressure pulsation behind the impeller of the centrifugal pump for evaluating the dynamic radial force and hydraulic turbulence and noise. In recent years, domestic and foreign scholars have studied the unsteady flow, pressure pulsation and radial force pulsation of centrifugal pumps at different positions such as inside the shell wall and outlet of the impeller on the surface under different working conditions through calculation methods such as high-frequency pressure sensor, LDV laser measuring instrument and CFD program [4][5][6]. However, in these calculations, the fluid is all water.…”
Section: Introductionmentioning
confidence: 99%